Preparing a Collaborative Health Workforce through Team-Building Training: A Pilot Reaction-Level Evaluation in Indonesia - Irwin Irwin; Gandes Retno Rahayu; Yoyo Suhoyo (Journal of Public Health and Pharmacy, 2026)
Introduction: Global health systems face challenges from fragmented services, high costs, and workforce shortages, impacting care quality. Interprofessional education (IPE) is a key strategy for preparing a collaborative workforce. According to ADDIE instructional design model, this study aimed to develop and implement a policy-relevant team-building training program to enhance collaboration, communication, and problem-solving skills among health professional students, supporting health system transformation goals. Methods: The program was developed through the five phases of the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. A needs assessment guided the design of interactive, experiential activities to improve teamwork competencies in interprofessional education. The training program was piloted for 16 hours (two separate days) with health professional students from diverse disciplines (N=11). A mixed-methods approach was implemented, while the quantitative data were collected via the reaction level of the adjusted Kirkpatrick-Phillips’ questionnaire to assess satisfaction scores, and qualitative data were collected through focus group discussions (FGDs). Results: The implementation of the team-building program significantly improved participants' teamwork skills, communication effectiveness, and overall group cohesion. Participants reported highly positive participant reactions and perceived teamwork enhancement. Conclusion: Applying the ADDIE model to structure team-building activities provides an effective educational strategy to foster interprofessional collaboration early in training. More importantly, such structured interventions represent a strategic investment in human resources for health, contributing to policy objectives for integrated and team-based care delivery.